SPIRITUAL EXPERIENCE AS A MECHANISM FOR ADDICTION RECOVERY AMONG INDIVIDUALS IN PESANTREN-BASED - Ishlakhatus Sa'idah; Wiryo Nuryono; Titin Indah Pratiwi; Najlatun Naqiyah (Jurnal Konseling Pendidikan Islam, 2026)
This research aims to explore spiritual experiences as an addiction recovery mechanism in individuals undergoing pesantren-based rehabilitation. This study uses a qualitative approach with an Interpretative Phenomenological Analysis (IPA) design to understand the life experiences of participants in interpreting the recovery process. Data were collected through semi-structured in-depth interviews, observations, and field records of individuals who are undergoing or have completed pesantren-based rehabilitation programs. The results show that spiritual experiences play an important role as an important mechanism in addiction recovery through four main dimensions, namely: spiritual awareness as a turning point for change, spiritual practice as a means of self-regulation against craving and prevention of relapse, religious community as a source of recovery support, and identity reconstruction as part of recovery transformation. These findings suggest that addiction recovery in the context of pesantren-based rehabilitation is not only related to the cessation of substance use, but is a psychospiritual process that involves a change in the meaning of life, self-control, communal support, and the formation of a new identity. This study proposes the concept of spiritual recovery mechanism as a theoretical contribution to expand the perspective of recovery capital in the study of addiction recovery.